(untitled) (International journal of artificial intelligence, 2024)
The article discusses the need for a competency-based approach in preparing students for professional activity in professional education, the goal of forming professional competence is to develop such components of the learner's self-understanding, assessment and management in the process of professional and personal development, and to prepare for work in secondary specialized and vocational educational institutions, to study the basics of general and specialized subjects, to achieve a positive attitude towards mastering general and specialized knowledge in professional activity, Development of pedagogical and technical-technological thinking as a method of identifying and solving problems in problematic situations inherent in production processes, the ability to apply individual educational methods in professional activities, the formation of reproductive and creative methods of educational-pedagogical and production activities, the development of important professional-pedagogical qualities in professional activities, namely, compassion, love for children and others, professional and personal to reveal the need for self-development.